Respuesta :
[tex]y = - \frac{3}{2}x + 5 \\ y = - \frac{3x}{2} + 5 \\ y = - \frac{3x}{2} + \frac{5 \times 2}{1 \times 2} \\ y = - \frac{3x}{2} + \frac{10}{2} \\ y = \frac{ - 3x + 10}{2} [/tex]
or you can turn it like this...
[tex]2y = 10 - 3x[/tex]
Answer:
[tex]2y+3x=10[/tex] is the standard form
Step-by-step explanation:
the standard form of the equation [tex]y=-\frac{3}{2} x+5[/tex]
Standard form of the equation is Ax+By =C
[tex]y=-\frac{3}{2} x+5[/tex]
Multiply the whole equation by 2 to remove the denominator 2
[tex]2y=-3x+10[/tex]
To get standard form we move -3x to the left side, add 3x on both sides
[tex]2y=-3x+10[/tex]
[tex]2y+3x=10[/tex] is the standard form